Innovative and sustainable governance model of rural transformation center in agribusiness projects: a conceptual paper - Raja Suzana Raja Kasim; Ariffin Awang; Zulazli Hashim
Realising that the National Vision and National Agricultural Policy to make Malaysia a major world producer of food